ТИЛ БИРЛИКЛАРИАРО ПАРАДИГМАТИК ВА СИНТАГМАТИК МУНОСАБАТЛАР МАСАЛАСИГА ОИД МУЛОҲАЗАЛА (Scientific journal of the Fergana State University, 2023)
The article deals with paradigmatics and paradigmatic relations, syntagmatics and syntagmatic relations, with which the systemic character  of  language levels and the systematic character of the language as a whole are organized.